Constraint management in database applications via Checker Framework - Armen J. Asatryan (АН Арм. ССР)
The paper presents concepts and ideas underlying an approach for constraint management in VLSI design database applications and designs °ows. In this approach constraints are de¯ned as scripts of EVA strongly typed scripting language and stored in meta{databases called check catalogue. Interaction of applications with check catalogue is supported by subsystem of DBMS called Checker Framework. Checker Framework provides facilities for creation, modi¯cation and deletion of the constraints and has several features that enhance the constraint management in database applications.
Keywords: Mathematics; Computer software